PUBLIC SPACES, SHARED STRUGGLES: : HOW GENDER SHAPES THE URBAN EXPERIENCE - Florencia Andreola, Silvia Tagliazucchi and Federica Rocchi, (Cadernos IS-UP, 2025)
Public spaces are often designed to be neutral and inclusive, yet they frequently fail to accommodate the diverse experiences of the people who use them. Women, and gender minorities face unique challenges in navigating urban environments, from safety concerns to the lack of amenities that consider their specific needs. The article explores the profound ways in which gender influences how individuals perceive, interact with, and move through urban landscapes. This paper highlights the often-overlooked link between urban design and gender equity. It reveals how public spaces – designed without considering lived experiences – can perpetuate fear, and restrict opportunities for participation in public life. Conversely, it examines how inclusive planning can create safer, more welcoming environments that empower all city dwellers. The research also unpacks the systemic biases embedded in traditional urban planning practices, offering a roadmap for change through participatory processes and innovative interventions. By addressing questions like “Who feels safe walking home at night?” and “Whose needs are prioritized in public transit?”, it calls for a shift in how we approach urban design, placing gender equity at the forefront of planning. The aim is to inspire a collective reimagining of cities as spaces where everyone – not just a privileged few – can thrive.